FRI0109 TEMPORAL CHANGES IN LUNG NODULES DETECTED IN INDIVIDUALS WITH RHEUMATOID ARTHRITIS WITH BIOLOGIC DMARD TREATMENTS. (13th June 2020) - Karadeniz, H.; Cingil, E.; Satiş, H.; Avanoğlu Güler, A.; Bilici Salman, R.; Atas, N.; Babaoglu, H.; Goker, B.; Haznedaroglu, S.; Ozturk, M. A.; Tufan, A.
Abstract : Background: Lung nodules in rheumatoid arthritis (RA), patients impose diagnostic and therapeutic challenges due to unpredictable outcome of these nodules. biologic (b) disease-modifying anti-rheumatic drugs (bDMARDs) are important therapeutic agents used in treatment of RA. There is hesitation about use of conventional synthetic DMARDs (csDMARD) and bDMARDs due to increased risk of nodules although their association remains unclear. There are scarce data on lung nodules observed in RA patients and systematic studies are needed. Objectives: The aim of this study is to evaluate effects of biologic treatments and conventional synthetic DMARDS on pulmonary nodules observed in rheumatoid arthritis patients. Methods: Electronic health records of RA patients who had had thorax computed tomography (CT) confirmed lung nodules in the last 5 years were retrospectively evaluated. Pre-treatment and post-treatment follow up CT images were meticulously examined for the number, size, attenuation, calcification, and cavitary formation. Demographic features, smoking status, disease characteristics and used medications were retrieved from file records. Clinical and laboratory findings, demographic features, treatment and follow-up duration, number of solid and cavitary nodules were compared between groups. Results: There were 21 patients in both biologic (11 females, mean age; 59.7±8.4) and csDMARD (12 females, mean age; 71.4±8.3) treated groups. There was no difference in frequency of nodule types and sizes between csDMARD and bDMARDs groups (table ) despite csDMARD users were remarkably older. Administered biologic treatments were anti-TNF-alpha in 8, tofacitinib in 7, rituximab in 4, and abatacept in 2 patients. The most common types of nodules were solid and cavitary nodules, observed in 17 and 8 patients, respectively in biologic users. Calcific nodules were present in three patients, and ground glass nodules were observed in a single patient. Nodules were multiple in 12 patients and solitary in 9 patients. Calcific and ground glass nodules were all solitary in our study. Cavitary and solid nodules were concurrent in five patients. Median follow duration was 14(5-55) months. Progression was observed in small number of patients; three patients in receiving aTNFα, and one in rituximab (figure ) and one in abatacept users. Interestingly none of patients receiving tofacitinib did not show progression. There was no difference regarding number of patients who progressed with either csDMARD or bDMARDs. None of the nodules showed malignant transformation within the observation period. Conclusion: In conclusion, risk of progression in lung nodules with biologic treatments is seem to be low, at least not more than csDMARD in short term and any malignant transformation was not observed in our study. References: [1]Esposito AJ, Chu SG, Madan R, Doyle TJ, Dellaripa PF. Thoracic Manifestations of Rheumatoid Arthritis. Clin Chest Med. 2019 Sep;40(3):545-560. doi:10.1016/j.ccm.2019.05.003. Epub 2019 Jul 6. Review. PubMed PMID: 31376890. Disclosure of Interests: None declared